On Folly Beach - White, Karen (Karen S.) (Thorndike, Me. : Center Point Pub., 2010)
Janie Hamilton purchases a local book store and discovers some old love letters tucked into a used book that brings her closer to the previous owner's sister, as they uncover what may have been a possible murder from the past.
Keywords: Booksellers and bookselling -- Fiction -- Folly Beach (S.C.); Large print books; Folly Beach (S.C.) -- Fiction; South Carolina -- Fiction; Fiction